The Poetry of Travel in Mario Campaña: A Theoretical Approach - L. C. Mussó (ESPOCH Congresses, 2023)
Abstract Mario Campaña's poetry is one of the most representative of contemporary Ecuador. This document aims to carry out a conceptual review based on different authors that exposes the importance of the work mentioned in the context of national letters. In the aforementioned context, a reflection on poetry is proposed, with a continuous line throughout its journey through successive books by the author. This article intends from a descriptive-exploratory nature, to present a rereading of the work through analysts who account for its connection with the trip.